Transformation of Bima local wisdom values through social studies e-book media - Ardiansyah, Suriadi; Komalasari, Kokom; Maryani, Enok; Wiyanarti, Erlina (Intelektual Pustaka Media Utama, 2024)
The development of postmodern-era technology in the world of education is increasingly sophisticated, thus impacting the character of students and their social environment. Technological progress negatively affects the lives of today's generation. When misuse of technology is widespread, it is imperative to strengthen cultural and religious filtration. So that the influence of globalization on technological development can be minimized. So as not to damage the cultural values and morality of students as the next generation of the nation. This study aims to explain the importance of transforming the values of Bima's local wisdom